Cone‑Beam Computed Tomography Assessment of Implant-Related Anatomy Landmarks of the Anterior Mandible in a Local Population - Sherazi, Surriya; Sharif, Mubashir; Khattak, Seema; khalid, Sana; Shahbaz, Madiha; Parveen, Wajeeha (Pakistan Armed Forces Medical Journal, 2026)
Objective: To examine the frequency, morphology, and location of the mandibular lingual foramen (MLF) lateral lingual foramen (LLF), and mandibular incisive canal (MIC) in a Pakistani population using cone-beam CT (CBCT). Study Design: A descriptive cross-sectional study. Place and Duration of Study: Department of Prosthodontics, Armed Forces Institute of Dentistry, Rawalpindi, from Sep 2023 to Aug 2024. Methodology: CBCT images of patients who presented to the Prosthodontics Department and fulfilled the inclusion criteria were enrolled consecutively in the study. NNT viewer software was used to analyze the MLF, LLF and MIC through the images. The analysis involved determining the presence and length of MIC and MLF. Along with this the position and classification of MLF, its distance relative to the alveolar crest and bottom part of mandible were also explored. Results: MLF was present in 707 subjects, of which the presence of a single medial LF was predominant. 401 patients had lateral lingual foramen observed; 76.31% had a single foramen, 21.45% had two foramina, and 2.24% had three foramina. Mandibular Incisive Canal (MIC) was present on both sides in 68.16% of the patients, while 71.29% of the samples had MIC on the left side. Conclusion: The results of this study reflect upon the higher frequency of MLF, LF and MIC in the local population of Pakistan.